The combined chemic-thermal processing as a way of increase of durability of details of exact mechanics - Писаренко, В.Г. (Problems of Tribology, 2014)
On the basis of analysis of modern technologies of chemic-thermal processing the offered combined technology for the complex providing of properties of wearproof, corrosive firmness and black of surface.